2021
DOI: 10.5194/gmd-2021-402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conservation laws in a neural network architecture: Enforcing the atom balance of a Julia-based photochemical model (v0.2.0)

Abstract: Abstract. Models of atmospheric phenomena provide insight into climate, air quality, and meteorology, and provide a mechanism for understanding the effect of future emissions scenarios. To accurately represent atmospheric phenomena, these models consume vast quantities of computational resources. Machine learning (ML) techniques such as neural networks have the potential to emulate compute-intensive components of these models to reduce their computational burden. However, such ML surrogate models may lead to n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Predicting fluxes instead of absolute concentrations ensures the preservation of mass balance between gas-and particle phases of IEPOX-SOA and prevents the model from deviating far from the outputs over longer time periods. Consistently, Strum et al 18 showed that by training the emulator to predict the flux information, nonphysical predictions by the emulators can be avoided.…”
Section: Wrf-chem and Dnn Model Training Datamentioning
confidence: 86%
See 4 more Smart Citations
“…Predicting fluxes instead of absolute concentrations ensures the preservation of mass balance between gas-and particle phases of IEPOX-SOA and prevents the model from deviating far from the outputs over longer time periods. Consistently, Strum et al 18 showed that by training the emulator to predict the flux information, nonphysical predictions by the emulators can be avoided.…”
Section: Wrf-chem and Dnn Model Training Datamentioning
confidence: 86%
“…Also, our training data are highly nonlinear and represent complex physics and chemistry. DNNs are artificial neural networks and are widely 2 Outputs (nmol/m 3 s −1 ) particle Iepox organosulfate Flux [Bin:1-20] iepoxosFluxes particle Tetrol Flux [Bin: [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] tetrolFluxes…”
Section: Deep Neural Network Architecture and Training Detailsmentioning
confidence: 99%
See 3 more Smart Citations